THE EFFECT OF YOGA ON THE REDUCTION OF BACK PAIN IN PREGNANT WOMENS TRIMESTER II AND III - Kuswati, Kuswati; Wahyuni, Tri; Sri Mulati, Triwik (Universitas Pahlawan Tuanku Tambusai, 2022)
Background : Back pain is a common discomfort in pregnancy. Back pain in pregnant women if not handled properly can lead to poor quality of life for pregnant women. So it is necessary to make efforts to overcome one of them with non-pharmacological therapy, namely pregnant yoga practice. Research Objectives: To determine the effect of pregnant yoga on reducing back pain in pregnant women in the second and third trimesters in the Kasreman Health Center Work Area, Ngawi Regency, East Java. Research Methods: This type of research is Quasi Experiment with (Pretest and post test without control group design). The population in this study was pregnant women in the second and third trimesters in the Kasreman Health Center Work Area, Ngawi Regency, East Java. A sample of 30 people was taken by purposive sampling technique. The dependent variable is pregnant yoga and the independent variable is the decrease in back pain for pregnant women in the second and third trimesters. The research instrument used NRS (Numerical Rating Scale). Data processing using editing, coding, tabulating with Wilcoxon test data analysis. Research Results: The results showed that back pain before doing yoga during pregnancy, most of the respondents experienced back pain with a minimum distribution scale of 1 (mild pain) category of pain scale as many as 5 respondents and a maximum distribution of scale with a pain scale category of 8 (severe pain) as many as 1 respondent, while After being given yoga, most of the pregnant women became the minimum distribution scale with a pain scale category of 0 (Mother Doesn't Feel Pain) as many as 9 respondents and a distribution scale that was maximum with a pain scale category of 5 (Medium Pain) as many as 2 respondents. The Wilcoxon statistic test showed that p value= 0.000 < (0.05) so that H1 is accepted. Conclusion: There is an effect of yoga on reducing back pain in pregnant women in the second and third trimesters in the Kasreman Health Center Work Area, Ngawi Regency, East Java. Key Word : Pregnancy Yoga, Back Pain in Second and Third Trimester